IMPLEMENTASI PEMASARAN DIGITAL dan APLIKASI AKUNTANSI UKM “BERBASIS ANDROID” BADAN USAHA MILIK DESA (BUMDes) Di Kecamatan TOMO – Kabupaten SUMEDANG - Djaddang, Syahril; Lysandra, Shanti; Derryawan, Derryawan; Salim, Fahruddin; Susilawati, Susilawati; Syam, M. Ardiansyah; Ety M, Endang; Nugraha, Muhammad (Capacitarea : Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) have a very important role for the economy in Indonesia. MSMEs are found in every region, for example traders in traditional markets, food stalls, craftsmen, home businesses, street vendors. There are 9 MSME business fields, namely Micro Enterprises, Small Enterprises and Medium Enterprises in Tomo District, Sumedang Regency, West Java, under the coordination of Bumdes and BumdesMa, which are divided into three categories of micro, small and medium enterprises. The purpose of implementing this PKM is to accelerate the process of developing digital marketing and the practice of preparing Android-based PSAK ETAP UKM financial reports; Help create access for the creation of new entrepreneurs who implement digital marketing and Android-based bookkeeping. The results of PKM through training, namely MSME participants who do not understand how to do marketing through digital marketing / e-Commerce, there are still many MSME actors in archiving and recording transactions in making financial reports, both manually and digitally. With this PKM activity, MSME actors have a strong interest and desire to learn how to implement marketing through online media/digital marketing, as well as make it easy for MSME actors to find out the performance of MSME businesses through BUMDes/BUMDesma for financial reports made digitally based on Android.